EphH, a unique epoxide hydrolase encoded by Rv3338 is involved in the survival of Mycobacterium tuberculosis under in vitro stress and vacuolar pH-induced changes - Garg, Tanu; Das, Swetarka; Singh, Shriya; Imran, Mohmmad; Mukhopadhyay, Atri; Gupta, Umesh D.; Chopra, Sidharth; Dasgupta, Arunava (Frontiers in Microbiology, 2023)
Introduction Mycobacterium tuberculosis (Mtb), one of the deadliest human pathogen, has evolved with different strategies of survival inside the host, leading to a chronic state of infection. Phagosomally residing Mtb encounters a variety of stresses, including increasing acidic pH. To better understand the host-pathogen interaction, it is imperative to identify the role of various genes involved in the survivability of Mtb during acidic pH environment. Methods Bio-informatic and enzymatic analysis were used to identify Mtb gene, Rv3338, as epoxide hydrolase. Subsequently, CRISPRi knockdown strategy was used to decipher its role for Mtb survival during acidic stress, nutrient starvation and inside macrophages. Confocal microscopy was used to analyse its role in subverting phagosomal acidification within macrophage. Results The present work describes the characterization of Rv3338 which was previously known to be associated with the aprABC locus induced while encountering acidic stress within the macrophage. Bio-informatic analysis demonstrated its similarity to epoxide hydrolase, which was confirmed by enzymatic assays, thus, renamed EphH. Subsequently, we have deciphered its indispensable role for Mtb in protection from acidic stress by using the CRISPRi knockdown strategy. Our data demonstrated the pH dependent role of EphH for the survival of Mtb during nutrient starvation and in conferring resistance against elevated endogenous ROS levels during stress environment. Conclusion To the best of our knowledge, this is the first report of an EH of Mtb as a crucial protein for bacterial fitness inside the host, a phenomenon central to its pathogenesis.